Atividade anti-Leishmania spp in silico e in vitro de oxadiazóis sintéticos - Pinheiro, Cristian Vicson Gomes (2024)
Globally, there are 1 billion people in endemic areas, with over 12 million people infected with leishmaniasis. However, it is a neglected disease, as the affected countries are underdeveloped and the available treatments are old, toxic, requiring a long period of parenteral administration and with limited efficacy. The oxadiazole heterocyclic ring has several biological activities already described in the literature, including leishmanicidal activity, making them candidates for further studies. A prospective study of scientific and technological nature was conducted. A review was conducted where eight studies were observed using oxadiazole molecules with potential leishmanicidal effects on various strains (Leishamania infantum, L. donovani, L. tropica, L. major, L. amazonensis, L. mexicana), highlighting that leishmanicidal activity may be related to the inhibition of important enzymes (GAPDH, Cysteine protease, and Pteridine Reductase) or with the increase in nitric oxide by cells infected with the parasite. However, there are only two patents using oxadiazoles to treat leishmaniasis, which highlights the difficulty in transferring technology from research to industry. Through pharmacokinetic ADME/TOX predictions, we demonstrate that the molecules have good intestinal absorption (All > 90%), have water-insoluble properties, and a high result in terms of permeability in Caco2 (High > 0.90 logPapp10-6cm/s), suggesting that oxadiazoles could be administered orally. Moreover, only two oxadiazole-derived molecules (2b and 2f) showed hepatotoxicity. In vitro, oxadiazoles showed relevant inhibitory activity of the DPPH radical, demonstrating potential antioxidant activity, with molecules 2g, 2h, and 2i respectively showing IC50 results of 6.90 μg/mL, 8.76 μg/mL, and 12.10 μg/mL. Regarding a possible leishmanicidal mechanism of action, the molecules were found to be inhibitors of the enzyme acetylcholinesterase, important for the formation of parasites' membranes containing choline, however, they did not demonstrate inhibition of Tripanotiona Reductase enzyme at the attributed concentrations. Finally, the studied molecules showed relevant leishmanicidal activity at various concentrations in the strains of L. braziliensis (2b with IC50= 180.8 μM) and L. infantum (2a, 2g, 2i with IC50 of 17.95 μM, 88.83 μM, and 30.86 μM, respectively). With cytotoxicity testing in RAW 264.7 macrophages, highlighted activity was observed for molecules 2a and 2i with CC50 values of 558 μM and 485.5 μM, and selectivity index (SI) of 31.08 and 17.86, respectively. These results made oxadiazoles 2a and 2i attractive for nanoencapsulation, and it was possible to obtain nanoparticles with an average size of 155.5nm and 127.7nm respectively. Based on the aforementioned, oxadiazoles become promising for more complex studies, opening perspectives for more selective and less toxic leishmanicidal agents.